Time and democracy: the humanism of praxis and utopic imaginaries in the current time - ASSELBORN, Carlos (Utopía y Praxis Latinoamericana, 2022)
The text recovers theoretical contributions that: a) reflect on the modes of time management in dependent and unequal societies and b) review the categorical framework of past memories and utopias or utopian discourses that have mobilized emancipatory praxis. Our interest is based on i) the need to expand the theoretical tools to think about ways of producing, managing and / or stealing time in political subjectivities; ii) point out how certain relationships between time and subjectivity can produce and / or deepen democratization processes; or shut them down and depower them. For this we assume the critique of utopian reason and the humanism of praxis developed by Franz Hinkelammert.